Los "Annales Dertusenses anni 1210 (olim Chronicon Dertusense II)" ("Díaz" 1188) edición, traducción, análisis lingüístico y estudio histórico - Martín-Iglesias, José Carlos 1968-; Iranzo Abellán, Salvador (2015)
This paper offers the first critical edition of the Chronicon Dertusense II (Diaz 1188), an annalistic compilation from 1097 to 1210 written in Latin in Mediaeval Catalonia. In addition, the article offers a linguistic analysis of the work, its translation, a detailed study of historical references and a detailed index allowing ease of consultation.
Keywords: Crítica literaria; Literatura latina medieval y moderna; Traducción